2007
DOI: 10.3322/canjclin.57.2.75
|View full text |Cite
|
Sign up to set email alerts
|

American Cancer Society Guidelines for Breast Screening with MRI as an Adjunct to Mammography

Abstract: including women with a strong family history of breast or ovarian cancer and women who were treated for Hodgkin disease. There are several risk subgroups for which the available data are insufficient to recommend for or against screening, including women with a personal history of breast cancer, carcinoma in situ, atypical hyperplasia, and extremely dense breasts on mammography. Diagnostic uses of MRI were not considered to be within the scope of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
913
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,294 publications
(965 citation statements)
references
References 80 publications
9
913
2
11
Order By: Relevance
“…Yearly screening with mri is now recommended in the United States for women with >20% to 25% lifetime risk of breast cancer 40 . In Canada, the most recent recommendations on this topic were published in 2007 by the National Hereditary Cancer Task Force 41 , whose panel recommended annual mg, complemented by mri where available, and added that whenever possible, imaging should be delivered by an experienced team of radiologists with expertise in mri, mg, and us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yearly screening with mri is now recommended in the United States for women with >20% to 25% lifetime risk of breast cancer 40 . In Canada, the most recent recommendations on this topic were published in 2007 by the National Hereditary Cancer Task Force 41 , whose panel recommended annual mg, complemented by mri where available, and added that whenever possible, imaging should be delivered by an experienced team of radiologists with expertise in mri, mg, and us.…”
Section: Discussionmentioning
confidence: 99%
“…Our trial was terminated early, after publication of guidelines from the American Cancer Society recommending screening mri as an adjunct to mg in high-risk women 40 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Ultrasound imaging has higher sensitivity than mammography in imaging dense breast but with low specificity in screening breast cancers. 4,5 Magnetic resonance imaging (MRI) was reported to have results correlated better with pathology findings than mammography and obtained promising results when dynamic contrast agents are applied. [6][7][8] However, MRI is expensive and exogenous agents are needed for better contrast.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of mammography 59% of the whole sample have a positive result, while MRI results say that only 15.2% of the sample have a positive result and after biopsy has performed the actual positive result is 13.3%. In a previous study [17], it was reported that MRI has high sensitivity ranging from 71% to 100% versus 16% to 40% for mammography in a high risk population. Screening mammograms alone, or screening breast ultrasounds alone, each found only a little more than half of the cancers.…”
Section: Discussionmentioning
confidence: 99%